2019
DOI: 10.9767/bcrec.14.3.3451.604-613
|View full text |Cite
|
Sign up to set email alerts
|

Operating Conditions and Composition Effect on the Hydrogenation of Carbon Dioxide Performed over CuO/ZnO/Al2O3 Catalysts

Abstract: A series of catalysts constituted of mixed copper and zinc oxides supported on alumina were prepared by co-precipitation method. The cooper content was in the 10-90 wt.% range. Their catalytic behavior in the hydrogenation of carbon dioxide to methanol was investigated at high pressure (up to 75 bars). The catalysts were characterized by elemental analysis, N2-adsorption, N2O-chemisorptions, and X-ray diffraction (XRD). The catalysts showed a clear activity in the hydrogenation reaction that could be correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“… 35 , 36 Furthermore, the peak appeared at ≈78 eV in Figure 2 e,f for all catalysts, corresponding to the characteristic peak of Al 2p spectra (Al 3+δ species). 17 , 37 , 38 This is shifted from low to high binding energy when compared to the original peak for pure Al 2 O 3 (Al 3+ species, 74.1 eV), according to previous literature studies. 37 , 38 As reported by Li et al 38 and Fu et al., 37 they explained that the shifted higher binding energy occurred from the chemical state of some Al 3+ species that increased to the state of Al 3+δ species to maintain the loss of electron because of Cu interacting with Al 2 O 3 (Al–O–Cu bond).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“… 35 , 36 Furthermore, the peak appeared at ≈78 eV in Figure 2 e,f for all catalysts, corresponding to the characteristic peak of Al 2p spectra (Al 3+δ species). 17 , 37 , 38 This is shifted from low to high binding energy when compared to the original peak for pure Al 2 O 3 (Al 3+ species, 74.1 eV), according to previous literature studies. 37 , 38 As reported by Li et al 38 and Fu et al., 37 they explained that the shifted higher binding energy occurred from the chemical state of some Al 3+ species that increased to the state of Al 3+δ species to maintain the loss of electron because of Cu interacting with Al 2 O 3 (Al–O–Cu bond).…”
Section: Resultssupporting
confidence: 78%
“…Furthermore, these results indicated that the hydrogen consumption of spent CZA catalysts in both hydrogenation reactions decreased with the increase in the number of Zn contents in catalyst composition [sCZA-L(CO) and sCZA-L(CO 2 )], contributing to the dwindling of CO and CO 2 hydrogenation ability. According to the literature studies, 1 , 4 , 17 , 47 , 48 the stability of Cu 0 sites during the CO and CO 2 hydrogenation is the main key factor for H 2 dissociation to adsorb feed molecules in the product formation step, resulting in the increase in the catalytic ability of Cu-based catalysts. In addition, the high Zn contents in the catalyst result in the formation of more surface Zn sites and blocking of the formation of Cu-ZnO interfaces, which acted as a source of the H atom storage for the intermediate molecules in the hydrogenation process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations